Fully heavy tetraquark bbc¯c¯: lifetimes and weak decays - Li, Gang; Wang, Xiao-Feng; Xing, Ye (The European physical journal. C, Particles and fields, 2019)
We study the lifetime and weak decays of the full-heavy S-wave 0 + tetraquark T { c ¯ c ¯ } { b b } . Using the operator product expansion rooted in heavy quark expansion, we find a rather short lifetime, at the order ( 0.1 - 0.3 ) × 10 - 12 s depending on the inputs. With the flavor SU(3) symmetry, we then construct the effective Hamiltonian at the hadron level, and derive relations between decay widths of different channels. According to the electro-weak effective operators, we classify different decay modes, and make a collection of the golden channels, such as T { c ¯ c ¯ } { b b } → B - K 0 B c - for the charm quark decay and T { c ¯ c ¯ } { b b } → B - D - for the bottom quark decay. Our results for the lifetime and golden channels are helpful to search for the fully-heavy tetraquark in future experiments.